PENERAPAN STRATEGI PEMBELAJARAN GROUP to GROUP EXCHANGE (GGE) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS XI IA SMA NEGERI 1 KUANTAN HILIR TAHUN PELAJARAN 2010/2011 - Rosmaini S; Nursal '; Resi Noprianti (Program Studi Pendidikan Biologi, 2011)
Has done research that aims to enhance motivation and students class he XI SMA N 1 Kuantan Hilir through the implementation of the school year 2010/2011 GGE learning strategies, research is a classroom action research conducted in January 2011. Research subjects are students of class XI science SMA N 1 Kuantan Hilir with the number of students in 41 people (10 men and 31 women). Parameter used is the motivation to learn (indicators: interest, relevance, expectation and outcome), the results of learning which consists of absorption of students, mastery learning, and teacher activity, the average motivation before implementation of the GGE strategy 3.24% (medium category) and after implementation of the GGE strategy 3.99% (high category) and the percentage increase 23.25%. Average percentage of students cycle I absorption is 75.48% (both categories) and the average percentage of students cycle II absorption is 81.09% (both categories). Mastery learning cycle with a percentage of 82.92% I and II cycle 100%. Average teacher activity cycle I 88.45% (category very good) and II cycle 100% (very good category). From the results of this research is that the application of learning GGE strategies can increase motivation and student learning outcomes in class SMA N 1 Kuantan Hilir regency TP 2010/2011.